The Ascent of Man - Bronowski, J. (Princeton Little, Brown and Company, 1973)
[This book] traces the development of science as an expression of the special gifts that characterize man and that have made him unique among animal species ... Whether discussing the evolution of mathematics, the rise of the republican scientist, or the place of science in the future, [the author of this book] approaches his subject with authority and grace. In the end, he gives us a new perspective, not just on science, but on civilization itself.-Dust jacket.
Including Colour Illustrations and Bibliography
Keywords: Science -- Science--Philosophy -- Human beings